2022
DOI: 10.1177/23220937221124745
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of 50 Years of Human Resource Management Research in Bangladesh: Retrospective Reflections and Forward Trajectories

Abstract: This article aims to determine the current status of human resource management (HRM) research in Bangladesh by reviewing papers published from 1971 to 2021 and offering recommendations for future research. An electronic search of the Scopus database was carried out using 17 keywords connected to HRM in combination with ‘Bangladesh’ and ‘Bangladeshi’. Finally, through a systematic literature review using the preferred reporting items for systematic reviews and meta-analyses (PRISMA), 25 empirical articles publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…The researcher emphasizes the relevance of both human resource management and change management in illuminating the development process. A survey of GHRM in Bangladesh by Islam et al (2022) reveals that no Bangladeshi HRM-related papers have been published in any A* listed journals according to the Australian Business Deans Council (ABDC) rating standards. It also showed that self-reported surveys are used by the majority of Bangladesh-based and HRM-related publications.…”
Section: 4contribution Of the Selected Researchesmentioning
confidence: 99%
“…The researcher emphasizes the relevance of both human resource management and change management in illuminating the development process. A survey of GHRM in Bangladesh by Islam et al (2022) reveals that no Bangladeshi HRM-related papers have been published in any A* listed journals according to the Australian Business Deans Council (ABDC) rating standards. It also showed that self-reported surveys are used by the majority of Bangladesh-based and HRM-related publications.…”
Section: 4contribution Of the Selected Researchesmentioning
confidence: 99%